Implementing tumor mutational burden (TMB) analysis in routine diagnostics: a primer for molecular pathologists and clinicians - Allgäuer, Michael; Budczies, Jan; Christopoulos, Petros; Endris, Volker; Lier, Amelie; Rempel, Eugen; Volckmar, Anna-Lena; Kirchner, Martina; Winterfeld, Moritz von; Leichsenring, Jonas; Neumann, Olaf; Fröhling, Stefan; et al. (Translational Lung Cancer Research, 2018)
Tumor mutational burden (TMB) is a new biomarker for prediction of response to PD-(L)1 treatment. Comprehensive sequencing approaches (i.e., whole exome and whole genome sequencing) are ideally suited to measure TMB directly. However, as their applicability in routine diagnostics is currently limited by high costs, long turnaround times and poor availability of fresh tissue, targeted next-generation sequencing (NGS) of formalin-fixed and paraffin-embedded (FFPE) samples appears to be a more feasible and straight-forward approach for TMB approximation, which can be seamlessly integrated in already existing diagnostic workflows and pipelines. In this work, we provide an overview of the clinical implications of TMB testing and highlight key parameters including pre-analysis, analysis and post-analytical steps that influence and shape TMB approximation by panel sequencing. Collectively, the data will not only serve as a field guide and state of the art knowledge source for molecular pathologists who consider implementation of TMB measurement in their lab, but also enable clinicians in understanding the specific parameters influencing TMB test results and reporting.